Demonstration of phage inhibitory action against Clostridium perfringens LMG 11264 within a complex chicken cecal microbiota in vitro - Wiese, Maria; Klaassens, Eline S.; Hatt, Volmar; Kreikamp, Angelique; Baak, Mirna L.; Heerikhuisen, Margreet; Van Der Vossen, Jos M. B. M. (Frontiers in Antibiotics, 2025)
IntroductionClostridium perfringens strains may cause foodborne illness, and 95% of human infections are linked to the consumption of contaminated meat, including chicken products. In poultry, C. perfringens infection may cause necrotic enteritis, and infections are associated with high mortality rates partially due to antibiotic resistance, which hampers efficient treatment. In-vitro screening approaches of alternative treatment options, for instance, specific phages, represent a promising strategy for the selection of novel interventions to combat infections.Material and methodsIn this study, we explored the application of a C. perfringens strain LMG 11264-specific phage #7 introduced at 104 pfu/mL to inhibit the growth of C. perfringens at 106 cfu/mL compared to two antibiotics (amoxicillin at 10 µg/mL and clindamycin at 10 µg/mL) within complex chicken cecal microbiota in vitro. Samples for gDNA isolation, qPCR, and metagenome sequencing were taken at the beginning and after 24 and 48 h of incubation.ResultsThe C. perfringens strain LMG 11264 proliferated within the untreated complex microbiota and reached levels of approximately 108 and 109 genome equivalents per mL after 24 and 48 h of incubation, respectively. The phage intervention with phage #7 inhibited the growth of C. perfringens LMG 11264 significantly; the inhibitory effects were similar to those exerted by the antibiotic intervention with amoxicillin and stronger than the inhibitory effects with clindamycin. In the absence of the C. perfringens challenge, we found a significant effect of amoxicillin (p = 0.040) or clindamycin (p = 0.000017) compared to the untreated control after 24 h of incubation, and the phage addition did not affect the alpha diversity expressed as Chao index significantly (p = 1). In addition, the endogenous C. perfringens in the chicken microbiota appeared insensitive to phage #7. The phage titer of phage #7 only increased in the presence of the inoculated C. perfringens strain LMG 11264. In conclusion, the i-screen model can be implemented to test the efficacy and specificity of phage therapy in vitro.